A review of cement sheath integrity evaluation techniques for carbon dioxide storage - Okhiria D. Udebhulu; Yetunde Aladeitan; Ricardo C. Azevedo; Giorgio De Tomi (Journal of Petroleum Exploration and Production Technology, 2023)
Abstract Cement sheath integrity is a critical concern in the successful implementation of geologic carbon capture and storage (CCS) projects. Conventional ordinary Portland cement (OPC) is not thermodynamically compatible with the carbon dioxide (CO2) present in CO2 storage media. When OPC cement sheaths interact with aqueous CO2, they undergo degradation, producing calcium bicarbonate. This bicarbonate readily dissolves in the formation aquifer and can create leakage pathways, compromising the integrity of the wellbores. This study comprehensively reviews the state-of-the-art techniques for evaluating cement sheath integrity, providing a comprehensive compendium of available methods in a single article. The paper’s objective is to support the deployment of successful CCS projects, facilitate the remediation of affected wellbores in CO2 storage systems, and offer guidelines for evaluating improved cement slurry designs and formulations. Additionally, the study identifies the factors that influence cement sheath integrity when exposed to aqueous CO2, including in-situ temperature and pressure, reservoir fluid characteristics, cement slurry formulations, and wellbore operations. Furthermore, various modes of mechanical failure in cement sheaths are identified, such as radial cracking, plastic deformation, inner and outer debonding, and channeling. Understanding these failure mechanisms is crucial for designing robust cementing strategies in CCS applications. Evaluation techniques for assessing the integrity of cement sheaths exposed to aqueous CO2 encompass a range of approaches. These include direct experimentation with samples that mimic the in -situ conditions of storage sites, well logging for monitoring leakages, analytical, numerical, and statistical modeling, and risk assessments. Direct experimentation plays a vital role in understanding the carbonation kinetics and changes in cement sheaths' mechanical and transport properties. Techniques such as scanning electron microscopy, back-scattered electron image detectors, energy-dispersive spectroscopy, mercury intrusion porosimetry, optical microscopy, X-ray diffraction, electrical resistivity imaging, electron probe microanalyzers, inductivity-coupled plasma optical emission spectrometry, X-ray computed microtomography, Raman spectroscopy, direct image correlation, and particle velocimetry are utilized for direct experimentation. Analytical and numerical modeling approaches include reactive transport modeling, multi-scale modeling, computational fluid dynamics (CFD), and artificial intelligence (AI)-based modeling. In field operations, the integrity of the cement sheaths can be evaluated using cement bond evaluation tools, pressure transient test tools, cement coring tools, or sustained casing pressure analysis. These techniques collectively enable a comprehensive assessment of the integrity of cement sheath exposed to aqueous CO2, aiding in optimizing and monitoring carbon storage systems. Every CO2 storage medium is unique. Optimal assessment of the cement sheaths' integrity of its wellbore systems, when exposed to aqueous CO2, would require a different combination of suitable evaluation techniques. Future studies should focus on developing standardized guidelines that combine laboratory testing, field-scale testing, and numerical modeling to predict the evolution of cement sheath integrity when exposed to aqueous CO2. Additional research is necessary to determine the optimal combinations of cement additives that enhance long-term resilience and resistance to carbonic acid attacks, enabling successful geologic sequestration. Furthermore, there are ample research opportunities to advance numerical modeling techniques for evaluating the effects of aqueous CO2 on cement sheath integrity and identifying potential failure mechanisms.